Spatial capital, cultural consumption and expatriate neighbourhoods in Hanoi, Vietnam - Yun, Hae Young; Kim, Jeehun; Ho, K. C. (Asia Pacific viewpoint, 2022)
Cities of the Global South constitute a wide band in terms of their integration into the global economy. For cities like Hanoi, the sustained influx of foreign direct investments has propelled them into playing increasingly important roles as manufacturing centres. Along with this new role is the influx of expatriate managers who watch overseas manufacturing subsidiaries. Our paper focuses on Korean expatriate neighbourhoods and their impacts on Hanoi. More specifically, we show how the presence of such communities has resulted in important changes in the host city, firstly in housing typology (such as the introduction of high‐rise mixed‐use complexes), and secondly, in cultural consumption. We argue that Korean privilege, cultural consumption practices, and the desire for support and solidarity within the Korean social network in Hanoi work to create new forms of city‐building knowledge, one that originates from the neighbourhoods of these new and rich settlers in the city. Such forms of knowledge subsequently go on to reshape the economic, cultural and social spaces in the globalising city.